STUDIES REGARDING THE POSTHARVEST QUALITY MANAGEMENT OF STRAWBERRIES - Adrian CHIRA; Lenuța CHIRA; Elena DELIAN; Ligia ION; Valentin Alexandru GHIORGHIU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The present study shows the main factors that influence the post-harvest quality management of strawberries. The study was carried out on 4 varieties of strawberries: Albion, Marmolada, Elsanta and Gorella, cultivated in the area of Vidra, Ilfov county, Romania. The fruits were harvested when about 90-95% of the surface of the fruit had the characteristic color of the variety. The storage period under modified atmosphere conditions was 14 days. A minimum of 7% soluble dry matter is recommended for strawberries and 10% would be excellent, as far as the consumer’s expectation is concerned. The total losses, determined at the end of storage, showed values between 10.4% for the Gorella variety and 13% for the Marmolada variety. The depreciation due to rot was caused by the pathogens Botrytis cinerea and Penicillium italicum and showed values between 2.6% for the Marmolada variety and 5.1% for the Elsanta variety.